2020
DOI: 10.1088/1361-6668/ab7c53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the sintering temperature on the microstructure and superconducting properties of MgB2 bulks manufactured by the field assisted sintering technique

Abstract: Magnesium diboride (MgB2) bulk superconductors may have practical applications as permanent magnets owing to their ability to trap larger fields than conventional ferromagnets and a transition temperature of 39 K that make them attractive for use in cryogen-free systems. Unlike the cuprate high temperature superconductors, grain boundaries in MgB2 act as pinning sites not weak links, and so show good current carrying ability in polycrystalline samples. This enables the materials to be processed using standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 34 publications
4
20
0
Order By: Relevance
“…The bulk was sintered at 1300 C and 50 MPa for 5 minutes. Further details of the sintering process can be found in [15]. The absolute trapped field potential of the sample was characterised by FCM utilising a 12T large bore magnet system with precise control of the bulk temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The bulk was sintered at 1300 C and 50 MPa for 5 minutes. Further details of the sintering process can be found in [15]. The absolute trapped field potential of the sample was characterised by FCM utilising a 12T large bore magnet system with precise control of the bulk temperature.…”
Section: Methodsmentioning
confidence: 99%
“…∆T c decreased from 1.7 K in unmodified MgB 2 to 0.6 K in the sample containing 10 wt.% Mg, as shown in Table 2. Matthews et al [11] reported a similar reduction in ∆T c in unmodified MgB 2 samples sintered at higher temperature. The authors attributed this to heterogeneities (composition and/or disorder) initially present in the as-received powder being annealed out at high temperature.…”
Section: Magnetic Measurementsmentioning
confidence: 67%
“…Sintering or Direct Current Sintering is a popular technique that has been used successfully to produce dense MgB 2 specimens by different research groups [7][8][9][10][11]. This technique consists in driving a high current (usually at a low voltage) through an assembly composed of a graphite die in which the powder is enclosed between two graphite punches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4a shows the benefit of identical temperature for 3 and 5 GPa where a threshold of resistivity appeared from 950 • C. The benefit of pressure in Figure 4b at 1.7 GPa probably derived from the high-density ceramics that were reached in this range of pressure. Resistivity values decreased systematically with increasing processing temperature, suggesting the MgB 2 lattice contains fewer defects and likely results in the superconductor having no parasitic phases [20,21]. Up to now, the majority of dense samples have been made by high-temperature and high-pressure (HT-HP) processes.…”
Section: Resistance Analysesmentioning
confidence: 99%